Phát triển cộng đồng học tập cho sinh viên sư phạm: Nghiên cứu thực trạng và định hướng tiếp cận tích hợp tại khu vực miền núi phía Bắc - Đoàn Thị Cúc, Đoàn Thị Cúc (Tạp chí Giáo dục, 2026)
Learning communities represent an important approach in teacher education, particularly in mountainous regions where organizational conditions and infrastructure remain limited. This study adopts a mixed-methods design, combining questionnaire-based surveys (n = 918 pre-service teachers; n = 112 lecturers), in-depth interviews, descriptive statistical analysis, and qualitative interpretation to examine the current development of learning communities among pre-service teachers and to identify appropriate directions for improvement. The findings indicate that learning communities have begun to emerge but remain fragmented, insufficiently structured, and not yet sustainable. Student participation tends to be short-term and contextdependent, while the integration of technology into learning activities has not been sufficiently effective. The results further suggest that, in mountainous contexts, learning communities largely operate at the level of participation and have not developed coherently in terms of awareness, organizational structure, and instructional support functions. These findings provide additional empirical evidence and reinforce an integrated approach to the development of learning communities. However, due to the limitations of the cross-sectional design and the reliance on participant-reported data, the findings should be further validated in future research.